Nigeria : Anambra Teachers - World Bank (Washington, DC, 2014)
Research suggests that teacher quality is the main school-based predictor of student achievement and that several consecutive years of outstanding teaching can offset the learning deficits of disadvantaged students (Hanushek and Rivkin, 2006; Nye et al, 2004; Park and Hannum, 2001; Rivkin et al, 2005; Rockoff, 2004; Sanders, 1998; Sanders and Rivers 1996; and Vignoles et al, 2000). However, it is not yet clear exactly which teacher policies can raise teacher effectiveness (Goldhaber, 2002 and Rivkin et al, 2005). Thus, devising effective policies to improve teaching quality remains a challenge. The eight policy goals includes the following headings: setting clear expectations for teachers; attracting the best into teaching; preparing teachers with useful training and experience; matching teachers' skills with students' needs; leading teachers with strong principals; monitoring teaching and learning; supporting teachers to improve instruction; and motivating teachers to perform.